2020
DOI: 10.3389/fspor.2020.584194
|View full text |Cite
|
Sign up to set email alerts
|

Physical Preparation in Female Rugby Codes: An Investigation of Current Practices

Abstract: Female sports have recently seen a dramatic rise in participation and professionalism world-wide. Despite progress, the infrastructure and general sport science provisions in many female sports are behind their male counterparts. From a performance perspective, marked differences in physical and physiological characteristics can be seen between the sexes. Although physical preparation practices for male athletes are known, there are currently no published literature pertaining exclusively to female athletes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 67 publications
(120 reference statements)
0
37
0
1
Order By: Relevance
“…Survey responses showed that 98% of respondents indicated that they evaluated sprint performance, presenting a higher frequency than previously reported (e.g., 77 AE 25% in rugby and American football [16][17][18]38 ). Of which 92% reported using the data to inform training practices.…”
Section: Evaluation Of Sprint Trainingmentioning
confidence: 67%
See 4 more Smart Citations
“…Survey responses showed that 98% of respondents indicated that they evaluated sprint performance, presenting a higher frequency than previously reported (e.g., 77 AE 25% in rugby and American football [16][17][18]38 ). Of which 92% reported using the data to inform training practices.…”
Section: Evaluation Of Sprint Trainingmentioning
confidence: 67%
“…9,20,22,25 Consistent with previous findings, performance development is being approached using combined methods of specific and non-specific training methods, targeting the underpinning determinants of sprint performance. 1618,38 However, the content (i.e., exercise selection, training load prescription) varied across practitioners, as previously reported in football cohorts (rugby and American football) and even in elite sprinters. 16,17,46…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations